THE IMPACT OF HOTEL RESPONSES TO ONLINE NEGATIVE REVIEWS ON CONSUMERS' PURCHASE INTENTION - Jeetesh Kumar; Sana Maidullah (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
This research investigates the hotel response strategies of businesses being responsive online to stimulate customers purchase intention in eWOM communications. Specifically, this study explores the online managerial responses in terms of length, speed, and relevance of management response to customer negative reviews and how customer personality moderates the purchase intention of the hotel. A non-probability convenience sampling technique was applied to collect 441 responses from Chinese residents who have made online hotel reservations and selected the hotel only after checking the online reviews and the hotel responses. The findings confirm that hotel response to negative reviews has an essential impact on 'consumers' purchase intention and consumer personality traits. Further, the research includes the practical implications for hotels to set up the reply format and carry out effective service recovery through different expression ways of negative reviews response.